Neoadjuvant outperforms adjuvant regimens in resectable advanced Chinese melanoma patients: lymph node preservation as a key immunological advantage - Hou, Shuguang; Zhao, Bolun; Zhang, Babo; Zhao, Luyang; Zhang, Hao; Chen, Yang; Zhang, Wanfu; Zhu, Guannan; Guan, Hao (Frontiers in Immunology, 2025)
BackgroundRegional lymphadenectomy was once considered as the standard treatment for melanoma patients with positive SLNB result, aimed at reducing the risk of recurrence and metastasis. However, recent researches have suggested multiple key roles of regional lymph node clusters in anti-tumor immune responses. Therefore, in the era of immunotherapy, whether lymph node dissection ultimately benefits patients remains to be determined, especially in acral melanoma, the leading subtype in east Asian population, which has a poorer response to immune checkpoint inhibitors (ICIs).MethodsWe retrospectively analyzed 172 patients with resectable advanced melanoma (stage III-IV, M1a) from a tertiary center and categorized them into four groups based on treatment regimens: immunotherapy group, observation group, neoadjuvant group, adjuvant group. In patients receiving immunotherapy (including immunotherapy group, neoadjuvant group, and adjuvant group), anti-PD-1 antibody was given accompanied with interferon-α1b.ResultsWith a median follow-up of 18.87 months, multivariable analysis confirmed significantly longer RFS for neoadjuvant versus adjuvant group. The adjusted HR was 2.02 (95% Cl 1.05–3.89, p= 0.035). Numerical improvements over immunotherapy and observation groups did not reach statistical significance, with p-values of 0.120 and 0.073 respectively. The 2-year RFS rate was significantly higher at 39.5% versus 13.8%. Notably, surgery-related adverse events occurred in 50.0% of patients (12.5% grade ≥3), with no significant differences observed among groups.ConclusionsThis study demonstrates that in Chinese patients with advanced melanoma, neoadjuvant therapy is associated with significantly prolonged RFS compared to adjuvant therapy, with suggestive but non-significant advantages against other approaches.